Study of New Jersey Coastal Inlets and Beaches: Interim Report on Hereford Inlet to the Delaware Bay Entrance of the Cape May Canal - United States Army Corps of Engineers, Philadelphia District, North Atlantic Division (United States Army Corps of Engineers, Philadelphia District, North Atlantic Division, 1972)
This report presents the results of a study of the navigation and shoreline erosion problems of the coastal inlets and beaches of New Jersey, from Hereford Inlet to the Delaware Bay entrance of the Cape May Canal. While the study area for this interim report stretches 16 miles along the southernmost portion of the NJ coast in Cape May County, the report is one of four interim studies conducted along the entire 126-mile coast of New Jersey. The scope or purpose of the study was to examine and evaluate beach recreation needs, problems related to navigation, coastal erosion, and damage caused by storm tides and waves in oceanfront areas. Purpose: To examine and evaluate beach recreation needs, problems related to navigation, coastal erosion, and damage caused by storm tides and waves in southern New Jersey oceanfront areas.